PELAYANAN KESEHATAN REPRODUKSI DI KOTA MEDAN : EVALUASI TERHADAP AKSES DAN KUALITAS PELAYANAN - SURJADI RIMBUN (JURNAL ILMIAH MAKSITEK, 2023)
Medan is one of the cities in North Sumatra has a population of mostly young people, where the number of young people in Medan City is 598,366 people. Among the total population, around 29,100 people experience reproductive health problems, namely the emergence of sexual diseases, both infectious and non-communicable. The high number of young people who experience reproductive disorders is caused by access to health services and health services that have not been maximized. This study used descriptive analytical method. The population of this study amounted to 29,100 people who experienced reproductive health problems, where reproductive health problems would cause sexual diseases. The population of this study amounted to 29,100 people who experienced reproductive health problems and who experienced obstacles in obtaining access and reproductive health services in Medan City, where the samples taken amounted to 59 residents who experienced reproductive health problems and who experienced obstacles in obtaining access and reproductive health services in Medan City. The results stated that the number of people who have a low level of reproductive health is the population in the East Medan District area which is on average in the age range of 15-19 years, where the average population who experience reproductive health problems is young women caused by reduced access to health services in the form of health workers, and reduced health services in the form of reduced emergency room services.